Towards a Pax Cubana: revolution, socialism and development in Havana’s Cold War foreign policy - Yordanov,Radoslav (2022)
Abstract This paper uses a wide array of original documents collected from Bulgarian, Czech, German, Hungarian, Polish, Romanian and Serbian diplomatic, party and security services archives, reflecting Havana’s foreign policy during the Cold War. The article’s narrative follows Cuba’s Cold War foreign policy in the 1970s. Through its multipolar archival research methodology, the paper aims to help us acquaint a more nuanced and fuller picture of the complex and evolving character of Cuba’s Cold War internationalism as seen through the eyes of Moscow’s East European allies, marking a clear departure from existing literature mostly engaging Soviet or American sources.